The Temporal Stability of Dividends and Stock Prices: Evidence from the Likelihood Function - DeJong, David N.; Whiteman, Charles H. (American Economic Review, 1991)
The debate over whether the expected present value of dividends adequately describes stock prices hinges in part on whether dividends are trend-stationary or integrated processes: it does not if dividends are trend-stationary; it does if they are integrated. This paper argues that classical statistical tests only indicate that there is not sufficient evidence to reject either specification and provides Bayesian analyses designed to reveal the relative support the data give to the two specifications. The analysis suggests that dividends and prices are more likely to be trend-stationary than integrated, leaving the determination of prices a puzzle.